2015
DOI: 10.5194/angeo-33-769-2015
|View full text |Cite
|
Sign up to set email alerts
|

In situ magnetotail magnetic flux calculation

Abstract: Abstract. We explore two new modifications of the magnetotail magnetic flux (F ) calculation algorithm based on the Petrinec and Russell (1996) (PR96) approach of the tail radius determination. Unlike in the PR96 model, the tail radius value is calculated at each time step based on simultaneous magnetotail and solar wind observations. Our former algorithm, described in Shukhtina et al. (2009), required that the "tail approximation" requirement were fulfilled, i.e., it could be applied only tailward x ∼ −15 R E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… Abbreviations of models: PR96 [ Petrinec and Russell , ], KS98 [ Kuznetsov and Suvorova , ], P98 [ Pudovkin et al , ], S98 [ Shue et al , ], B00 [ Boardsen et al , ], L10 [ Lin et al , ], W13 [ Wang et al , ], and SG15 [ Shukhtina and Gordeev , ].…”
Section: Empirical and Numerical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“… Abbreviations of models: PR96 [ Petrinec and Russell , ], KS98 [ Kuznetsov and Suvorova , ], P98 [ Pudovkin et al , ], S98 [ Shue et al , ], B00 [ Boardsen et al , ], L10 [ Lin et al , ], W13 [ Wang et al , ], and SG15 [ Shukhtina and Gordeev , ].…”
Section: Empirical and Numerical Modelsmentioning
confidence: 99%
“…The model has no predetermined analytical form, and consequently, its results for any given condition cannot be reproduced without full access to the model. Shukhtina and Gordeev [] (SG15) developed a model to determine the magnetopause position at the terminator plane in the high‐latitude regions as a function of P dyn , B z , and Ψ.…”
Section: Empirical and Numerical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Shukhtina et al [] we developed the PR96 approach such that the magnetopause radius and the corresponding MTF value F 0 are computed using magnetotail and solar wind measurements for each particular time. In Shukhtina and Gordeev [, hereafter SG'15] two modifications of the method, F 1 and F 2 , suitable in the inner magnetosphere, were introduced. In section 2 we overview all three estimates, after which we present their calibration and validation (the main goal of this paper).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the shape of the MP is asymmetric due to the cusp regions. We, therefore, used models with an analytical formula, taking into account the pressure imbalance due to the Earth's dipole tilt angle ( ) that reproduces the cusp regions resulting in an asymmetric MP shape (Lin et al, 2010;Shukhtina & Gordeev, 2015). Zhong et al (2014) have shown that the Earth's dipole moment has been decaying over the past 1.5 centuries.…”
Section: Data and Analysismentioning
confidence: 99%